2014
DOI: 10.5005/jp-journals-10029-1075
|View full text |Cite
|
Sign up to set email alerts
|

Medications in Thai Patients with Oral Lichen Planus, Oral Lichenoid Drug Reaction and Glossitis

Abstract: Introduction:Medications have been widely used in the dental patients for the treatment of their systemic diseases. In fact, those drugs have some side-effects to many organs and also the oral cavity. The aim of our study was to investigate the relationship between medications and oral lichen planus (OLP), oral lichenoid drug reaction (OLDR) and glossitis (GT) in Thai patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…A recent study of medications in Thai patients with oral lichen planus or oral lichenoid drug reaction showed that most of the patients with oral lesions took more than one medication. Antihypertensive drugs were the most commonly used drugs by Thai patients with oral lesions (17). Our study also showed that most of our patients were taking mul-Histopatološkim pregledom lezija pacijenata s OLL-om povezanim s lijekovima ustanovljeno je da je histopatološka dijagnoza oralnih lezija varirala -kod sedmero pacijenata dijagnosticiran je OLP/OLDR u suglasju s pet slučajeva OLPa, u tri slučaja radilo se o OLP-u, a trojici pacijenata dijagnosticirana je kronična nespecifična upala.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A recent study of medications in Thai patients with oral lichen planus or oral lichenoid drug reaction showed that most of the patients with oral lesions took more than one medication. Antihypertensive drugs were the most commonly used drugs by Thai patients with oral lesions (17). Our study also showed that most of our patients were taking mul-Histopatološkim pregledom lezija pacijenata s OLL-om povezanim s lijekovima ustanovljeno je da je histopatološka dijagnoza oralnih lezija varirala -kod sedmero pacijenata dijagnosticiran je OLP/OLDR u suglasju s pet slučajeva OLPa, u tri slučaja radilo se o OLP-u, a trojici pacijenata dijagnosticirana je kronična nespecifična upala.…”
Section: Discussionsupporting
confidence: 53%
“…Nedavno istraživanje u Tajlandu o lijekovima pacijenata s oralnim lihenom planusom ili oralnom lihenoidnom reakcijom na lijek, pokazalo je da većina njih s oralnim lezijama uzima više od jednog lijeka. Najčešći su antihipertenzivi (17). Naše istraživanje također je pokazalo da većina naših pacijenata s OLL-om uzima više lijekova i to uglavnom antihipertenzive i hipolipidemike.…”
Section: Raspravaunclassified
“…Most Thai patients with OLDR take multiple medications, such as hypolipidemics and antihypertensives . Oral hypoglycemics, non‐steroidal anti‐inflammatory drugs (NSAIDs) and antimalarials can also cause OLDR .…”
Section: Introductionmentioning
confidence: 99%
“…5 Most Thai patients with OLDR take multiple medications, such as hypolipidemics and antihypertensives. 5,8 Oral hypoglycemics, nonsteroidal anti-inflammatory drugs (NSAIDs) and antimalarials can also cause OLDR. 9 The aim of the present study was to investigate the correlation between the oral manifestations, medications, ANA and DIF patterns in patients diagnosed with OLP, OLL and OLDR lesions.…”
mentioning
confidence: 99%
“…A recent study showed that most Thai patients with OLP or OLDR took more than one medication. Antihypertensives and hypolipidemics were the most commonly used . In general, most elderly patients have multiple systemic diseases and are taking more than one medication.…”
Section: Discussionmentioning
confidence: 99%